2007
DOI: 10.1097/fpc.0b013e3280ea77cd
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in the amino acid transporters LAT1 and LAT2 in relation to the pharmacokinetics and side effects of melphalan

Abstract: The study confirmed that these transporter genes are highly conserved, particularly in the coding sequences. Genetic variation in 4F2hc, LAT1, and LAT2 does not appear to be a major cause of inter-individual variability in pharmacokinetics and of adverse reactions to melphalan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 38 publications
0
25
1
Order By: Relevance
“…The polymorphism 2677G>T/A of ABCB1 gene was recently correlated with increase in k a of GAB. Although LAT2 transporter activity has been associated with GAB absorption, its gene ( SLC7A8 ) is highly conserved and there are no studies showing that polymorphisms could change gene expression or transporter function . Studies showed that LAT1 transporter plays a role in GAB distribution through the blood‐brain and blood‐retinal barriers .…”
Section: Discussionmentioning
confidence: 99%
“…The polymorphism 2677G>T/A of ABCB1 gene was recently correlated with increase in k a of GAB. Although LAT2 transporter activity has been associated with GAB absorption, its gene ( SLC7A8 ) is highly conserved and there are no studies showing that polymorphisms could change gene expression or transporter function . Studies showed that LAT1 transporter plays a role in GAB distribution through the blood‐brain and blood‐retinal barriers .…”
Section: Discussionmentioning
confidence: 99%
“…While our work was in progress, a similarly designed study was published that failed to detect an association between SNPs in the genes encoding LAT1, LAT2, and 4F2hc and gastrointestinal toxicity following HDM chemotherapy (17). Although the patient population used was more heterogeneous than the one in our study and included individuals with diseases other than multiple myeloma, the more likely reason for these discrepant results was the lack of representation in their analysis of SNPs from the very large first intron of SLC7A5 , such as rs4240803.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly half of these children died of brain herniation and many who survived were permanently disabled [2]. The Clinic for Special Children, built in 1989, has since become a medical home to 79 MSUD patients [5,6,42]. Early work at the Clinic was focused on integrating metabolic management into general pediatric practice [2,43].…”
Section: Discussionmentioning
confidence: 99%